Erythrina subumbrans (Hassk) Merr. (Fabaceae) Inhibits Insulin Resistance in the Adipose Tissue of High Fructose-Induced Wistar Rats - Susilawati E; Levita J; Susilawati Y; Sumiwi SA (Dove Medical Press, 2024)
Elis Susilawati,1,2,* Jutti Levita,3,* Yasmiwar Susilawati,4 Sri Adi Sumiwi3 1Doctoral Program in Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 2Faculty of Pharmacy, Bhakti Kencana University, Bandung, Indonesia; 3Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia; 4Department of Biology Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, Indonesia*These authors contributed equally to this workCorrespondence: Jutti Levita, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Padjadjaran University, Sumedang, West Java, 46363, Indonesia, Tel +6222-84288888 Ext 3510, Email jutti.levita@unpad.ac.idBackground: The twigs and roots of Erythrina subumbrans (Hassk). Merr. Was reported to possess antidiabetic activity by reducing the activity of α-glucosidase and α-amylase. TNF-α is a pro-inflammatory cytokine in obesity and diabetes mellitus (DM). It inhibits the action of insulin, causing insulin resistance. Adiponectin is an anti-inflammatory peptide synthesized in white adipose tissue (WAT) and its high levels are linked with a decreased risk of DM. However, information about the effect of Erythrina subumbrans (Hassk). Merr. on insulin resistance are still lacking.Purpose: To obtain the effects of the ethanol extract of E. subumbrans (Hassk) Merr. leaves (EES) in improving insulin resistance conditions.Methods: The leaves were collected at Ciamis, West Java, Indonesia, and were extracted using ethanol 96%. The effects of EES were studied in fructose-induced adult male Wistar rats by performing the insulin tolerance test (ITT) and assessing blood glucose, TNF-α, adiponectin, and FFA levels. The number of WAT and BAT of the adipose tissues was also studied. The total phenols and flavonoids in EES were determined by the spectrophotometric method and the presence of quercetin in EES was analyzed using the LC-MS method.Results: EES significantly reduced % weight gain, TNF-α levels, and increased adiponectin levels in fructose-induced Wistar rats. EES significantly reduced the FFA levels of fructose-induced Wistar rats and significantly affected the formation of BAT similar to that of metformin. All rats in EES and metformin groups improved insulin resistance as proven by higher ITT values (3.01 ± 0.91 for EES 100 mg/kg BW; 3.01 ± 1.22 for EES 200 mg/kg BW; 5.86 ± 3.13 for EES 400 mg/kg BW; and 6.44 ± 2.58 for metformin) compared with the fructose-induced group without treatment (ITT = 2.62 ± 1.38). EES contains polyphenol compounds (2.7638 ± 0.0430 mg GAE/g extract), flavonoids (1.9626 ± 0.0152 mg QE/g extract), and quercetin 0.246 μg/mL at m/z 301.4744.Conclusion: Erythrina subumbrans (Hassk). Merr. extract may have the potential to be further explored for its activity in improving insulin resistance conditions. However, further studies are needed to confirm its role in alleviating metabolic disorders.Keywords: adiponectin, anti-diabetes, Erythrina, inflammation, insulin resistance, tumor necrosis factor